Present state of Vascular Surgery in Pakistan - Omer Ehsan (Pakistan Journal of Medical & Health Sciences, 2024)
Vascular surgery is still struggling to establish as a speciality in Pakistan. There are only a few centres in main cities of Pakistan where vascular surgery is practiced as a separate specialty and the number of trained vascular surgeons is also very limited. Most of these centres are either in military or private hospitals. Vascular surgery was recognised by College of Physicians and Surgeons CPSP) as a second fellowship in 2015 and at present there are only 7 recognised centres with 10-11 supervisors. CPSP has held the fellowship, FCPS vascular surgery, exam since 2019 and there is now an addition ofaround 25 – 30 FCPS vascular surgery consultants who are in their early post fellowship years. Most of them are working in Pakistan while some have gone abroad for job or further training.Those working in Pakistan are also struggling to find a vascular setup to work in